Confectioneries and condiments intake were associated with decreased birth Weight in the Universiti Sains Malaysia birth cohort study - Mohamed, Hamid Jan (2012)
Introduction: Maternal nutrition is one of the important element in determining fetal growth and subsequent heal/h. Improvement in socio-economy status is one of the factors that increase the diversity of food intake during pregnancy. However. unheal/hy food consumption during pregnancy may affect mother's health and also the growth of the fetal thus leading to the development of chronic disease during adulthood. Objective: The objective of this study is to investtgate the association of maternal food groups intake with birth size at term. Methods: A total of 108 pregnant women at late pregnancy, aged 19-40 years were recruited from the antenatal cliniC of Universiti SBins Malaysia Hospital. These subjects were recruited from the ongoing Universiti Sains Malaysia Birth Cohort Study. EthiCal approval was obtained from The Universiti Sains Malaysia Human Research EthiCs Committee. Nutrients and foods intake were examined using a validated and focally adapted semi-quantitative food frequency questionnaire. Maternal medical history and anthropometry was recorded accordingly. Birth weight. birth length and head circumference were measured using the standard protocol. Data 1vere analyzed using multiple linear regression method by controlling for possible confounders. Results: Among all food groups, organ meats and fruits were associated with increased birth weight (p<0.05 and p<0.01), respectively and birth length (p<0.05 and p<O 05), respectively. Fruits and green leafy vegetables were associated with increased head circumference (p<O 01 and p<0.05). respectively. In contrast, confectioneries and condiments intake were associated with decreased birth weight (p<0.05 and p<0.001). respec/tvely. Conclusions: These findings suggest/he beneficial effects of nulnent dense foods on fetal growth, whereas highly processed food exerts detrimental effects on fetal growth. Such an effect may have tong term health consequences to an individual's fife.